دور الاعلان فى ترويج المنتوج السياحي العراقي دراسة تحليلة لمضمون الاعلانات السياحية على موقع وزارة السياحة والاثار العراقية على شبكة الانترنت للمدة من1/9/2013 لغاية 30/12/2013 - على حمود حسن, طارق (Al-Adab Journal, 2018)
Tourist advertisement is considered one of the important means of communication with the tourist .lt introduces him with the programme presented by the tourist organizations and reflects his needs and desires e.g. The need to travel ,the motives of learning ,researching and observing. Thus, tourist advertisement is considered an important means of developing tourism.